Contemporary feminist utopianism - Sargisson, Lucy, 1964- (Women and politics (Routledge (Firm)), 1996)
Sargisson explores current debates around feminist theory, utopian studies and deconstruction. She argues for utopianism as a way out of the dilemma of contemporary feminism, as well as a way of conceptualizing its current situation.